Pengembangan Lembar Kegiatan Siswa (LKS) Berbasis Keterampilan Berpikir Kritis Untuk Mendukung Implementasi Kurikulum 2013 - M. Rahmad Syalehin; Sri Hartini; Suriasa Suriasa (Berkala Ilmiah Pendidikan Fisika, 2015)
Learning physics only to training remember and understand aspect the causes of passive students and inhibit the development of thinking on a higher level. One reason for the development of curriculum 2013 is training critical thinking skills. Therefore, research that aims to develop critical thinking skills worksheets based on the subject matter of heat to support the implementation of curriculum 2013. The specific aims of this study describes: (1) the validity of student’s worksheet, (2) critical thinking skills of students after using the student’s worksheet, and (3) student's response to student’s worksheet. This type of research is the development of research ADDIE model includes the analysis, design, development, implementation, and evaluation. Research subjects are 30 students of class VII-F Junior High School 24 Banjarmasin. Collecting data through sheet of validity, sheet of critical thinking skills, interviews, observation,  questionnaire responses, and documentation. Data were analyzed by quantitative descriptive. Results showed (1) the validity of student’s worksheets based critical thinking skills in a very valid category and in the category high reliability, (2) critical thinking skills in the excellent category, and (3) student's response to student’s worksheet in the excellent category. Be concluded that the student’s worksheet based critical thinking skills developed in the proper category.